Stratigraphy of the Khuvsgul Group, Mongolia - Anttila, Eliel; Macdonald, Francis; Bold, Uyanga (Mongolian Geoscientist, 2021)
The Khuvsgul Group (Khuvsgul Province, Mongolia) is a Late Neoproterozoic to Cambrian carbonate-dominated succession that includes minor glacial diamictite and one of the largest known ore-grade phosphate deposits in the world. These strata, which have experienced low-grade metamorphism, are exposed in the Khoridol-Saridag Range on the western margin of Lake Khuvsgul. Since 2017, new geologic mapping and field studies have been conducted in the Khuvsgul region. During the course of this work, it has become necessary to restructure the stratigraphic framework of the Khuvsgul Group in order to better facilitate geologic mapping, stratigraphic observations, and regional correlations. We have divided the lower Khuvsgul Group into four distinct formations spanning the Cryogenian and Ediacaran, each of which encompass strata associated with the Sturtian glaciation, Cryogenian non-glacial interlude, Marinoan glaciation, and basal Ediacaran transgression respectively. The phosphorites of the Khuvsgul Group are now included within a new distinct formation, while the overlying Cambrian carbonates and siliciclastic rocks have been further subdivided to streamline mapping and correlation efforts. The stratigraphic framework outlined below will simplify identification and differentiation of Khuvsgul Group rocks in the field and provide a foundation for the interpretation of Khuvsgul Group strata within the context of the changing climatic, tectonic, and paleoenvironmental conditions of the late Neoproterozoic and early Cambrian.